GENERAL TECHNICAL AND INFORMATION EDUCATION IN FRAMEWORK EDUCATION PROGRAMME FOR BASIC EDUCATION AND ACROSS THE CURRICULUM - KVAPIL, Ludek; PROCHAZKOVA, Ivona (Trends in education, 2008)
General technical and information education in the new Czech school system creates the need to update the educational means, looking for the innovated methods and forms of work and application of cross-curricular approach. The successful realization of Framework Education Programme presupposes also development of general technical and information literacy in a wider civil context.
Keywords: technical education; information education; Framework Education Programme